MENGIDENTIFIKASI PERJUANGAN RAHMAH EL-YUNUSIAH DALAM BIDANG PENDIDIKAN PEREMPUAN DI MINANGKABAU DAN PEGARUHNYA DI DINIYYAH PUTRI PADANG PANJANG SAMPAI SEKARANG - Fatmawati (Majalah Ilmiah Tabuah: Ta`limat, Budaya, Agama dan Humaniora, 2020)
The main issue of this problem is Rahmah El Yunusiah's struggle in preparing Diniyyah Putri and her influence until now. The purpose of this study was to analyze the role of Rahmah Elyunusiah in women's education in Minangkabau and her role in managing Diniyyah Putri. The method used is the library research method with a study approach with the domain of analysis. With Rahmah el Yunusiah's findings, she succeeded in changing the community's perspective on the importance of women's education, and it was designed for a special school for girls (Diniyyah Putri). The educational thoughts expressed in Diniyyah Putri are still alive and well and are constantly changing and adapting to their times.